William A. Oldridge collection of George Washington's headquarters staff writings - Oldridge, William A.
Chiefly transcripts of correspondence collected and edited by Oldridge. Correspondents include Elias Boudinot, Horatio Gates, William Grayson, Alexander Hamilton, Edward Hand, Robert Hanson Harrison, David Humphreys, George Johnston, John Laurens, James McHenry, Richard Kidder Meade, Thomas Mifflin, Stephen Moylan, Joseph Reed, Tench Tilghman, and Jonathan Trumbull.
Includes correspondence, writings, and other papers of Oldridge concerning the location of papers and illustrations of Washington's headquarters staff and historical accounts from the original material.
Transcripts of originals in various repositories.
Collector.
Collection material in English.
Finding aid available in the Library of Congress Manuscript Reading Room and at
Volume 9 contains an index to the correspondence in volumes 1 to 8.
Keywords: Boudinot, Elias, -- 1740-1821 -- Correspondence; Gates, Horatio, -- 1728-1806 -- Correspondence; Grayson, William, -- 1736-1790 -- Correspondence; Hamilton, Alexander, -- 1757-1804 -- Correspondence; Hand, Edward, -- 1744-1802 -- Correspondence; Harrison, Robert Hanson, -- 1745-1790 -- Correspondence; Humphreys, David, -- 1752-1818 -- Correspondence; Johnston, George, -- 1750-1777 -- Correspondence; Laurens, John, -- 1754-1782 -- Correspondence; McHenry, James, -- 1753-1816 -- Correspondence; Meade, Richard Kidder, -- 1746-1805 -- Correspondence; Mifflin, Thomas, -- 1744-1800 -- Correspondence; Moylan, Stephen, -- 1737-1811 -- Correspondence; Reed, Joseph, -- 1741-1785 -- Correspondence; Tilghman, Tench, -- 1744-1786 -- Correspondence; Trumbull, Jonathan, -- 1740-1809 -- Correspondence; Washington, George, -- 1732-1799.; United States. -- Continental Army; United States -- History -- Revolution, 1775-1783.; Collectors